2004
DOI: 10.1111/j.1464-410x.2004.05172.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term outcome of the endoscopic subureteric implantation of polydimethylsiloxane for treating vesico‐ureteric reflux in children: a retrospective analysis of the first 195 consecutive patients in two European centres

Abstract: OBJECTIVE To determine the long‐term efficacy of endoscopically implanting polydimethylsiloxane (PDS, Macroplastique®, Uroplasty BV, Geleen, the Netherlands) for treating vesico‐ureteric reflux (VUR) in children. PATIENTS AND METHODS We retrospectively reviewed the records of 195 children treated with PDS over the past 10 years in two European centres (Netherlands and UK) and conducted follow‐up investigations where deemed necessary. In the Dutch centre patients were treated according to a prospective approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 18 publications
1
16
0
3
Order By: Relevance
“…Una alternativa muy utilizada, blanda y a base de silicona es el polidimetilsiloxano, mejor conocido como Macroplastique ® . [17][18][19] Los resultados a corto plazo después de la utilización de este agente son similares a los de otras sustancias, 15 mientras que a largo plazo son algo inferiores y van desde el 77% hasta el 84%, 17 aunque en este estudio, los pacientes asintomáticos eran dados de alta sólo después de un año del tratamiento inicial. La explicación científica de estos resultados a largo plazo es que el macroplástico es un compuesto de partículas de diferente tamaño y las más pequeñas son las causantes de una posible migración a distancia.…”
Section: Reflejo Vesicoureteral Tratamiento Endoscópico / 351unclassified
“…Una alternativa muy utilizada, blanda y a base de silicona es el polidimetilsiloxano, mejor conocido como Macroplastique ® . [17][18][19] Los resultados a corto plazo después de la utilización de este agente son similares a los de otras sustancias, 15 mientras que a largo plazo son algo inferiores y van desde el 77% hasta el 84%, 17 aunque en este estudio, los pacientes asintomáticos eran dados de alta sólo después de un año del tratamiento inicial. La explicación científica de estos resultados a largo plazo es que el macroplástico es un compuesto de partículas de diferente tamaño y las más pequeñas son las causantes de una posible migración a distancia.…”
Section: Reflejo Vesicoureteral Tratamiento Endoscópico / 351unclassified
“…It is reabsorbed and exchanged with a reactive transudate containing fibroblasts, which then facilitate its encapsulation [6]. Other previous studies have reported success rates ranging from 70% to 92% by endoscopic administration using PDS, and a recent meta-analysis reported a success rate of 76.6% [1][2][3]. In addition, long-term follow-up studies have demonstrated that the long-term success rate of PDS is much greater than that of other agents [5,7,8].…”
Section: Discussionmentioning
confidence: 92%
“…Markedly low rates of complications after endoscopic administration of bulking agents have been reported. Rates of erosions and occurrence of contralateral VUR as postoperative complications have been reported in 0.6% and 2.1%, respectively [1]. In particular, the occurrence of ureteral obstruction was reported in less than 1% of injected ureters using PDS [1,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los dos primeros están actualmente en desuso: el colágeno por malos resultados debido a reabsorción precoz y el Macroplastique por dificultad técnica en la inyección (2) . Para la población pediátrica, la inyección endoscópica de Deflux® se ha ido transformando en la mejor alternativa para el tratamiento endoscópico del RVU, por su facilidad de manejo en la inyección, disponibilidad en el mercado y durabilidad en el tiempo (6) . El tamaño de las microesferas de copolí-mero de dextranómero en ácido hialurónico alcanza entre 80 y 250 micrones, lo que lo hace no migrable; existen trabajos que reportan mejoría con 10 años de seguimiento (7) .…”
Section: Discussionunclassified